Leverage and other informal pressures in community psychiatry in England. - Canvin, K; Rugkåsa, J; Sinclair, J; Burns, T (2013)
PURPOSE: Informal practices aimed at managing psychiatric patients in the community setting fall outside legal and policy provision or guidance. "Leverage" is an informal practice whereby practitioners attempt to influence patients' treatment adherence by, for example, making patients' access to subsidised housing conditional upon adherence to treatment or by making treatment adherence a condition of patients' avoidance of financial control. Lower rates of leverage are reported in the UK compared to the USA, possibly due to differences between the US and European social welfare systems. These differences raise questions as to the international comparability of leverage practices described in the literature. The study aimed to capture patients' experiences and perceptions of pressures and to explore (a) whether "leverage" can be distinguished from other pressures, and (b) how a concept of leverage derived from patient experiences in England might fit with the literature to date. In this article we present the different types of pressure that we identified from patients' accounts, and a set of criteria derived for the purpose of distinguishing between these different types of pressure. METHOD: Twenty-nine qualitative interviews with a purposive subsample from a study of leverage in the English mental health system were analysed. RESULTS: Participants reported a range of what can be classified as both leveraged and non-leveraged pressures. These were perceived as pressures to adhere to treatment, as well as "staying well." Leveraged pressures were distinguishable from non-leveraged pressures by the presence of three features: conditionality, a lever and direct communication. CONCLUSIONS: The portrayal of "leverage" in the current literature does not fully capture patient experiences of pressure. Our analysis offers a clearer concept of leverage and other pressures that influence patients, and which may have different legal, ethical and clinical implications.